Screening for common mental disorder in elderly residents in the countryside: a cross-sectional study - Tainara Catozzi Denardi; Roselma Lucchese; Graciele Cristina Silva; Moisés Fernandes Lemos; Valéria Pagotto; Johnatan Martins Sousa; Ivânia Vera (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To estimate the prevalence of common mental disorders and their associated factors in the elderly in a municipality in the countryside of the Brazilian Midwest. Methods: Quantitative, observational, cross-sectional approach research, conducted with 218 elderly people. Results: The prevalence of the common mental disorder among the elderly was 25.1%; in the univariate analysis, it was higher in females (35.4%), in the age group of 80 years or older (46.1%), brown skin color (30.2%), widowed (42.6%), illiterate (47.6%), and retired (27.6%). In the multiple analysis, the variables female gender (p<0.006), age 80 years or older (p<0.036), dissatisfaction with life (p<0.009), lack of social interaction (p=0.017), and dysfunctional family (p=0.021) remained associated with CMD. Conclusion: The results revealed are helpful and contribute to the reinforcement of the need for mental health care in this population extract so growing worldwide.